Inhaled nitric oxide decreases pulmonary endothelial nitric oxide synthase expression and activity in normal newborn rat lungs. Issue 1 (18th February 2016) - Hua-Huy, Thông; Duong-Quy, Sy; Pham, Hoa; Pansiot, Julien; Mercier, Jean-Christophe; Baud, Olivier; Dinh-Xuan, Anh Tuan
Inhaled nitric oxide (iNO) is commonly used in the treatment of very ill pre-term newborns. Previous studies showed that exogenous NO could affect endothelial NO synthase (eNOS) activity and expression in vascular endothelial cell cultures or adult rat models, but this has never been fully described in newborn rat lungs. We therefore aimed to assess the effects of iNO on eNOS expression and activity in newborn rats. Rat pups, post-natal day (P) 0 to P7, and their dams were placed in a chamber containing NO at 5 ppm (iNO-5 ppm group) or 20 ppm (iNO-20 ppm group), or in room air (control group). Rat pups were sacrificed at P7 and P14 for evaluation of lung eNOS expression and activity. At P7, eNOS protein expression in total lung lysates, in bronchial and arterial sections, was significantly decreased in the iNO-20 ppm versus control group. At P14, eNOS expression was comparable among all three groups. The amounts of eNOS mRNA significantly differed at P7 between the iNO-20 ppm and control groups. NOS activity decreased in the iNO-20 ppm group at P7 and returned to normal levels at P14. There was an imbalance between superoxide dismutase and NOS activities in the iNO-20 ppm group at P7. Inhalation of NO at 20 ppm early after birth decreases eNOS gene transcription, protein expression and enzyme activity. This decrease might account for the rebound phenomenon observed in patients treated with iNO. Inhaled NO decreases endogenous NO synthesis and favours rebound pulmonary hypertension after inhaled NO withdrawal http://ow.ly/WNDq2